2020
DOI: 10.1002/term.3091
|View full text |Cite
|
Sign up to set email alerts
|

ST2 silencing aggravates ventricular remodeling and chronic heart failure in rats by mediating the IL‐33/ST2 axis

Abstract: Heart failure appears to be a severe public health problem affecting millions of people worldwide. Knowledge of the molecular mechanism contributing to ventricular remodeling would allow for earlier prevention of heart failure. Evidence exists reporting the involvement of IL‐33 and ST2 and in heart remodeling. Thus, this study aims to delineate the effects of ST2 on chronic heart failure (CHF) via the IL‐33/ST2 axis. Coronary artery ligation was employed to simulate CHF in rats, which were characterized by tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Soluble suppression of tumorigenesis-2 (sST2), a member of the interleukin-1 receptor family, is a marker of ventricular mechanical stress. The secretion of sST2 in serum is markedly increased when cardiomyocytes are injured, myocardial fibrosis, or ventricular remodeling [ 59 , 60 ]. The prognostic value of sST2 in both acute and chronic HF has been proven.…”
Section: Resultsmentioning
confidence: 99%
“…Soluble suppression of tumorigenesis-2 (sST2), a member of the interleukin-1 receptor family, is a marker of ventricular mechanical stress. The secretion of sST2 in serum is markedly increased when cardiomyocytes are injured, myocardial fibrosis, or ventricular remodeling [ 59 , 60 ]. The prognostic value of sST2 in both acute and chronic HF has been proven.…”
Section: Resultsmentioning
confidence: 99%
“…The beneficial and harmful effects of the IL-33/ST2 axis in patients with CAD are debatable ( 34 , 42 44 ). Although several studies have reported the role of the IL-33/ST2 axis in CAD from a genetic perspective, the results remain controversial.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial showed that the 5‐year mortality rate of hospitalized patients with CHF is as high as 50%, which seriously affects the physical and mental health of patients (Ma et al, 2020). Ventricular remodeling (VR) after acute myocardial infarction (AMI) is the main pathogenesis of CHF, which regulates the prognosis of AMI patients (Zhao et al, 2020). Actively exploring how to prevent VR after AMI, and delay the pathophysiological process of CHF is an inevitable choice to effectively improve the prognosis of patients with AMI and prevent and cure CHF.…”
Section: Introductionmentioning
confidence: 99%